2011
DOI: 10.1007/s10811-011-9654-7
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characterization of free-floating and attached green macroalgae Ulva spp. in the Yellow Sea of China

Abstract: During the summer of 2008 and 2009, massive algal blooms repeatedly broke out in the Yellow Sea of China. These were undoubtedly caused by the accumulations of one or more species in the macroalgal genus Ulva. In previous reports, morphological observation indicated that the species involved in this phenomenon is Ulva prolifera but molecular analyses indicated that the species belongs to an Ulva linza-procera-prolifera (LPP) clade. Correct identification of the bloom species is required to understand and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…The main floating green mat species in the YS from 2008 to 2011 was U. linza, which was identified by rbcL analysis (e.g., UL380,382,388,715,720). These samples were identified as U. prolifera in previous studies, which belongs to the same clade as the YS green tide species from 2008 and 2009 (e.g., HM046604, HM584763) (Liu et al 2010c, Duan et al 2012. The floating green mats from the Qingdao coast (UL592, 596) and culture-derived samples from the YS (UL663, 664) were identified as U. linza.…”
Section: Molecular Phylogenetic Analysismentioning
confidence: 74%
“…The main floating green mat species in the YS from 2008 to 2011 was U. linza, which was identified by rbcL analysis (e.g., UL380,382,388,715,720). These samples were identified as U. prolifera in previous studies, which belongs to the same clade as the YS green tide species from 2008 and 2009 (e.g., HM046604, HM584763) (Liu et al 2010c, Duan et al 2012. The floating green mats from the Qingdao coast (UL592, 596) and culture-derived samples from the YS (UL663, 664) were identified as U. linza.…”
Section: Molecular Phylogenetic Analysismentioning
confidence: 74%
“…This result confirmed that the green tides in the Yellow Sea were dominated by a single species, U. prolifera, for the last five years. Although U. compressa and U. pertusa were also reported in some studies [12,18], the number of samples is really small (5 and 3, respectively) compared with the large number of U. prolifera samples (181 samples).…”
Section: Resultsmentioning
confidence: 85%
“…Based on morphological characteristics and molecular phylogenetic analyses, Duan et al [18] distinguished three freefloating Ulva species, namely, U. prolifera, U. compressa, and U. pertusa; species diversity of the Yellow Sea freefloating Ulva appeared to be greater than previously thought. Tian et al [19] pointed out that a succession of free-floating Ulva species, including U. compressa, U. flexuosa, and LPP complex, appeared in Rudong coastal areas, and the LPP strain was the same as the dominant Ulva species (U. prolifera) of the Yellow Sea green tides in 2008.…”
mentioning
confidence: 98%
“…1 was also described producing many branches mainly confined at the basal part (Ogawa et al 2013), and the branching manner coincided with U. partita. There are many field surveys of Ulva based on morphological and molecular phylogeny in Europe (Mareš et al 2011, Wolf et al 2012, Oceania (Kraft et al 2010, Kirkendale et al 2013, Micronesia (O Kelly et al 2010), North America (Guidone et al 2013), and Asia (Duan et al 2012, Bast et al 2014. However, U. partita has only been collected from the Japanese seashore.…”
Section: Discussionmentioning
confidence: 99%